Study From Home: An Analysis of Learning Difficulties of Biology in Junior High School Students During Online Learning - Rahmayumita, Restesa; Hidayati, Nurkhairo (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2023)
This research aims to discover students' learning difficulties during online learning, especially in science and biology subjects. This study used a descriptive method with a survey technique on the eighth-grade students at SMPN Siak Hulu. The research sample was obtained using a multilevel sampling technique with 191 students. The research instrument used a validated online learning difficulties questionnaire comprising 36 items. The data collection technique was done by distributing online questionnaires via Google Forms and then analyzed descriptively. The results showed that the level of student learning difficulties during online learning was in the medium category, with a percentage of 69.27. The conclusion obtained from the results of this study is that class VIII students of SMPN Siak Hulu experience learning difficulties during online learning in biology science subjects, especially at the level of understanding the material.ABSTRAK: Tujuan dari penelitian ini adalah untuk mengetahui kesulitan belajar siswa selama pembelajaran online khususnya pada mata pelajaran IPA biologi. Penelitian ini menggunakan metode deskriptif dengan teknik survei pada siswa kelas VIII di SMPN Siak Hulu. Sampel penelitian diperoleh menggunakan teknik sampling bertingkat yang berjumlah 191 orang. Instrumen penelitian menggunakan angket kesulitan belajar online yang telah divalidasi dan terdiri dari 36 item. Teknik pengumpulan data dilakukan dengan menyebarkan angket online melalui google form kemudian dianalisis secara deskriptif. Hasil penelitian menunjukkan tingkat kesulitan belajar siswa selama pembelajaran online berada pada kategori sedang dengan persentase sebesar 69.27. Kesimpulan yang diperoleh dari hasil penelitian ini bahwa siswa kelas VIII SMPN Siak Hulu mengalami kesulitan belajar selama pembelajaran online pada mata pelajaran IPA biologi terutama pada tingkat pemahaman materi.